A study on L-threonine and L-serine uptake in Escherichia coli K-12 - Khozov, Andrey A.; Bubnov, Dmitrii M.; Plisov, Eugeny D.; Vybornaya, Tatiana V.; Yuzbashev, Tigran V.; Agrimi, Gennaro; Messina, Eugenia; Stepanova, Agnessa A.; Kudina, Maxim D.; Alekseeva, Natalia V.; Netrusov, Alexander I.; Sineoky, Sergey P. (Frontiers in Microbiology, 2023)
In the current study, we report the identification and characterization of the yifK gene product as a novel amino acid carrier in E. coli K-12 cells. Both phenotypic and biochemical analyses showed that YifK acts as a permease specific to L-threonine and, to a lesser extent, L-serine. An assay of the effect of uncouplers and composition of the reaction medium on the transport activity indicates that YifK utilizes a proton motive force to energize substrate uptake. To identify the remaining threonine carriers, we screened a genomic library prepared from the yifK-mutant strain and found that brnQ acts as a multicopy suppressor of the threonine transport defect caused by yifK disruption. Our results indicate that BrnQ is directly involved in threonine uptake as a low-affinity but high-flux transporter, which forms the main entry point when the threonine concentration in the external environment reaches a toxic level. By abolishing YifK and BrnQ activity, we unmasked and quantified the threonine transport activity of the LIV-I branched chain amino acid transport system and demonstrated that LIV-I contributes significantly to total threonine uptake. However, this contribution is likely smaller than that of YifK. We also observed the serine transport activity of LIV-I, which was much lower compared with that of the dedicated SdaC carrier, indicating that LIV-I plays a minor role in the serine uptake. Overall, these findings allow us to propose a comprehensive model of the threonine/serine uptake subsystem in E. coli cells.